Fire safety issues in underground spaces: a need for regulatory evolution – French, Swiss and Hong Kong SAR, China (Hong Kong) contexts. Issue 1 (March 2021) - Moreau, B; Deffayet, M; Chan, I; Lam, F; Chau, P; Bettelini, M; Ng, F; Au, G
Abstract: Current regulations and operational safety requirements impose onerous constraints that make it difficult to be fulfilled by practical design of underground projects acceptable to all stakeholders. The ACUUS working group on fire safety of underground spaces intends to gather and share information on the ways how fire safety is taken into account and managed in different countries. This article presents the first work carried out within this working group. Regulatory contexts in France, Switzerland and Hong Kong SAR, China (Hong Kong) are presented, highlighting the current limitations. With their similarities and differences, the French, Swiss and Hong Kong contexts reveal a need to improve and to develop their respective regulations to allow pragmatic solutions without compromising fire safety. Underlying principles that condition fire safety requirements are defined in order to develop new approaches to overcome the aforementioned limits.